2021
DOI: 10.1101/gr.265900.120
|View full text |Cite
|
Sign up to set email alerts
|

Orc4 spatiotemporally stabilizes centromeric chromatin

Abstract: The establishment of centromeric chromatin and its propagation by the centromere-specific histone CENPA is mediated by epigenetic mechanisms in most eukaryotes. DNA replication origins, origin binding proteins, and replication timing of centromere DNA are important determinants of centromere function. The epigenetically regulated regional centromeres in the budding yeast Candida albicans have unique DNA sequences that replicate earliest in every chromosome and are clustered throughout the cell cycle. In this s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 84 publications
(108 reference statements)
0
8
0
Order By: Relevance
“…9b ). An increase in Cse4 levels could be an outcome of Cse4 loading at anaphase in C. albicans 63 , 64 . Finally, we analyzed the integrity of the mitotic spindle, as mentioned previously, in CSA6 PSD mutant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9b ). An increase in Cse4 levels could be an outcome of Cse4 loading at anaphase in C. albicans 63 , 64 . Finally, we analyzed the integrity of the mitotic spindle, as mentioned previously, in CSA6 PSD mutant.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study from our laboratory, Mcm7 has been identified as a subunit of the kinetochore interactome in a basidiomycete yeast Cryptococcus neoformans 95 . Another subunit of the Mcm2-7 complex, Mcm2, is involved in regulating the stability of centromeric chromatin in C. albicans 64 . Considering the growing evidence of the role of Mcm2-7 subunits beyond their canonical, well-established roles in DNA replication, the serendipitous identification of Mcm7 as a regulator of genome stability in our screen is striking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no evidence of tRNA gene expression going down during these stages of development. However, tRNA genes are known to play a role in remodeling chromatin and act as insulators or harbor origins of replication in other organisms ( Su et al 2020 ; Sreekumar et al 2021 ). Modules 1 and 9 are the only other modules that are significantly closing.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that depending on the types of mitoses, the players might differ in performing a non-canonical function. More examples of such non-canonical functions (Sreekumar et al, 2021; Varma et al, 2012), suggest how proteins organize between various processes to maintain cellular homeostasis. A series of evidence have established an interplay between errors in the spindle alignment with ageing and aneuploidy leading to the development of cancer and neurodegenerative diseases (Cheng et al, 2008; Knoblich, 2010; Lancaster & Knoblich, 2012; Manzano-Lopez et al, 2019; Yamashita et al, 2007).…”
Section: Discussionmentioning
confidence: 99%